Neurovascular Complications of the Upper Extremity Following Cardiovascular Procedures - Beutel, Bryan G.; Lifchez, Scott D.; Melamed, Eitan (Journal of Hand and Microsurgery, 2016)
Background Cardiovascular procedures are common and are trending toward endovascular interventions. With this increase in endovascular procedures, there is also increasing awareness of upper extremity morbidity resulting from treatment.Methods Articles indexed within PubMed between the years 1975 and 2015 that discussed such complications were reviewed.Results Percutaneous radial artery access can lead to nerve ischemia, especially in the setting of an incomplete arterial arch, whereas radial artery harvesting for bypass surgery more commonly causes frank tissue ischemia and radial neuropathy. Transulnar catheterization may cause ischemic hand injuries, while transbrachial angiography has resulted in compartment syndrome. Injuries to the nerves themselves often result from surgical equipment, such as sternal retractors, or from patient positioning leading to compression of the ulnar nerve. For percutaneous radial artery access, the incidence of ischemic injury is as high as 24%, whereas nerve injury is too rare to be estimated. In the setting of radial artery harvesting, ischemic injury is limited to case reports, and radial neuropathy is estimated to occur in as many as 25% of patients at discharge. Open heart surgery is the primary setting in which equipment or patient positioning plays a role, affecting 10% of patients with brachial plexus injuries and 15% with ulnar neuropathies.Conclusion Complications following cardiovascular interventions are varied and are typically associated with specific procedures. Careful preoperative and postoperative assessments of patients may aid in preventing, minimizing, and treating these often undiagnosed complications.
Keywords: upper extremity; hand; cardiovascular; procedures; complications